أثر التقيد بكفاية رأس المال على الحد من القروض المصرفية المتعثرة دراسة حالة لعينة من البنوك العربية خلال الفترة 2006- 2010 (مجلة الواحات للبحوث والدراسات, 2015)
One of the goals that the bank seeks to achieve higher levels of profitability, and this can only be done by reducing potential losses as much as possible (including from the risk of financial deficit) at the same time maintaining the safety of the banking through its compliance with various financial indicators. Accordingly, we find that the bank struggling to reduce  the risk of fianacial deficit,  and it strives to raise the solvency  ratio. This study aims to identify the impact of  the capital of risk  under the Basel Committee to reduce the financial deficit through ratios for sample analysis Arab banks during the study period 2006 - 2010 based on informations  extracted  from the annual reports of these banks, and we came in this study that  the capital of risk affect the deficit loans and has a role in reducing them, as the increase inthe bank's capital adequacy affect loans Troubled banking and contribute to reduction;but not permanently there may be other factors to the reduction  of deficit loans Key words : The capital of risk, deficit loans, Basel I ,Basel II